Battery packaging material, method for producing battery packaging material, and battery
By forming an acid-resistant film on the surface of the barrier layer of the packaging material for battery, and by optimizing specific peak strength ratios, the problem of insufficient adhesion between the acid-resistant film and adjacent layers in the packaging material for battery is solved, and long-term density is achieved Excellent combination and improved acid resistance, suitable for packaging materials for large batteries.
Patent Information
- Application Number
- CN202211025634.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2017-07-19
- Filing Date
- 2018-07-19
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2038-07-19
AI Technical Summary
In the long-term use of the barrier layer of the existing packaging material for batteries, especially in electric vehicles and hybrid electric vehicles, there is a problem that the acid-resistant film has insufficient adhesion to its adjacent layers, resulting in the electrolyte adhesion. performance degraded.
Using a laminated body of a substrate layer, a barrier layer and a hot melt resin layer composed at least in sequence, an acid-resistant coating is formed on at least one side of the barrier layer, and the acid-resistant coating is ensured by a time-of-flight ion mass spectrometry analysis. The specific peak intensity ratio of the elastic coating is in the range of 6 to 120 or 7 to 70 to optimize long-term adhesion.
It achieves excellent long-term adhesion under the condition of electrolyte adhesion, improves the acid resistance and service life of battery packaging materials, and is especially suitable for packaging materials for large batteries such as electric vehicles and hybrid electric vehicles.
Smart Images

Figure CN115172953B_ABST
Abstract
Description
[0001] This case is filed on July 19, 2018 、Application number is 201880047739.4 (PCT / JP2018 / 027188) , divisional application for invention titled "Battery Packaging Material, Method for Manufacturing Battery Packaging Material, and Battery". Technical Field
[0002] The present invention relates to a battery packaging material, a method for producing the battery packaging material, and a battery. Background Art
[0003] Currently, various types of batteries have been developed. In these batteries, it is necessary to encapsulate battery elements composed of electrodes, electrolytes, etc. with packaging materials, etc. As battery packaging materials, metal packaging materials are often used.
[0004] In recent years, with the high performance of electric vehicles, hybrid electric vehicles, personal computers, cameras, mobile phones, etc., there is a demand for batteries with various shapes. In addition, batteries are also required to be thinner and lighter. However, the currently commonly used metal packaging materials are difficult to adapt to the diversification of battery shapes. In addition, since they are made of metal, the lightweight of packaging materials is also limited.
[0005] Therefore, as a battery packaging material that can be easily processed into various shapes and can be reduced in thickness and weight, a film-like laminate having a base layer / barrier layer / thermofusible resin layer laminated in this order has been proposed (for example, see Patent Document 1).
[0006] In such a film-like battery packaging material, a recess is generally formed by molding, and battery elements such as electrodes and electrolyte are arranged in the space formed by the recess. The heat-fusible resin layers are heat-fused to each other to obtain a battery with the battery elements accommodated inside the battery packaging material.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: Japanese Patent Application Publication No. 2008-287971 Summary of the invention
[0010] Technical problem to be solved by the invention
[0011] When water enters the battery, it sometimes reacts with electrolytes to generate acidic substances. For example, the electrolyte used in lithium-ion batteries contains fluorine compounds (LiPF6, LiBF4, etc.) as electrolytes. It is known that when fluorine compounds react with water, hydrogen fluoride is generated.
[0012] The barrier layer of the battery packaging material formed by the film-like laminate is usually composed of metal foil, etc., and there is a problem that the barrier layer is easily corroded when it comes into contact with acid. As a technology for improving the acid resistance of such battery packaging materials, a technology is known to use a barrier layer with an acid-resistant film formed on the surface by chemical surface treatment.
[0013] Conventionally, various methods are known as chemical reaction surface treatment for forming an acid-resistant film, such as chromate treatment using a chromium compound such as chromium oxide and phosphoric acid treatment using a phosphoric acid compound.
[0014] However, the inventors of the present invention have found through repeated studies that the long-term adhesion between the conventional barrier layer having an acid-resistant film and the layer adjacent to the side provided with the acid-resistant film (i.e., the adhesion at the interface between the acid-resistant film and the layer in contact therewith) may become insufficient. More specifically, there is a case where the adhesion becomes insufficient due to the adhesion of the electrolyte to the battery packaging material.
[0015] In addition, batteries, especially those used in electric vehicles, hybrid electric vehicles, etc., are large batteries with long service life, and therefore require long-term adhesion. In this specification, the so-called long-term refers to the battery life required for vehicles such as electric vehicles and hybrid electric vehicles, for example, 6 to 20 years, and more specifically, about 15 to 20 years.
[0016] Under such circumstances, the main object of the present invention is to provide a battery packaging material having an acid-resistant film barrier layer with excellent long-term adhesion. In addition, the present invention also aims to provide a method for producing the battery packaging material and a battery using the battery packaging material.
[0017] Technical solutions for solving technical problems
[0018] The inventors of the present invention have conducted intensive research to solve the above-mentioned technical problems. As a result, it was found that the following battery packaging material has excellent long-term adhesion when an electrolyte is attached, although it has an acid-resistant film on the surface of the barrier layer. The battery packaging material is composed of a laminated body having at least a substrate layer, a barrier layer, and a heat-fusible resin layer in this order, and has an acid-resistant film on the surface of at least one side of the barrier layer. When the acid-resistant film is analyzed by time-of-flight secondary ion mass spectrometry, PO3 - The peak intensity P PO3 Relative to CrPO4 - The peak intensity P CrPO4 Ratio P PO3 / CrPO4 In the range of 6 to 120.
[0019] In addition, the inventors of the present invention have also found that the following battery packaging material has excellent long-term adhesion when an electrolyte is attached, although it has an acid-resistant film on the surface of the barrier layer. The battery packaging material is composed of a laminated body having at least a base layer, a barrier layer, and a heat-fusible resin layer in this order, and has an acid-resistant film on the surface of at least one side of the barrier layer. When the acid-resistant film is analyzed by time-of-flight secondary ion mass spectrometry, the acid-resistant film from PO2 - The peak intensity P PO2 Relative to CrPO4 - The peak intensity P CrPO4 Ratio P PO2 / CrPO4 In the range of 7 to 70.
[0020] The inventors of the present invention have found that a barrier layer having such an acid-resistant coating can maintain adhesion for a long period of time and is particularly useful as a packaging material for large batteries used in vehicles such as electric vehicles and hybrid electric vehicles.
[0021] The present invention was completed through further research based on these findings.
[0022] That is, the present invention provides the following aspects of the invention.
[0023] Item 1. A battery packaging material,
[0024] The invention is composed of a laminated body having at least a base material layer, a barrier layer, and a heat-fusible resin layer in this order.
[0025] The barrier layer has an acid-resistant film on at least one surface thereof.
[0026] When the above acid-resistant film was analyzed by time-of-flight secondary ion mass spectrometry, the PO3 - The peak intensity P PO3 Relative to CrPO4 - The peak intensity P CrPO4 Ratio P PO3 / CrPO4 In the range of 6 to 120.
[0027] Item 2. The battery packaging material according to Item 1, wherein at least a surface of the barrier layer on the side of the heat-fusible resin layer has the acid-resistant coating.
[0028] Item 3. The battery packaging material according to Item 2, wherein the acid-resistant film and the heat-fusible resin layer are laminated with an adhesive layer interposed therebetween.
[0029] Item 4. The battery packaging material according to Item 3, wherein the resin constituting the adhesive layer has a polyolefin skeleton.
[0030] Item 5. The battery packaging material according to Item 3 or 4, wherein the adhesive layer contains an acid-modified polyolefin.
[0031] Item 6. The battery packaging material according to any one of Items 3 to 5, wherein a peak derived from maleic anhydride is detected when the adhesive layer is analyzed by infrared spectroscopy.
[0032] Item 7. The battery packaging material according to Item 6, wherein the acid-modified polyolefin of the adhesive layer is maleic anhydride-modified polypropylene.
[0033] The thermally fusible resin layer contains polypropylene.
[0034] Item 8. The battery packaging material according to any one of Items 3 to 7, wherein the adhesive layer is a cured product of a resin composition containing at least one selected from a compound having an isocyanate group, a compound having an oxazoline group, and a compound having an epoxy group.
[0035] Item 9. The battery packaging material according to any one of Items 3 to 8, wherein the adhesive layer is a cured product of a resin composition containing a curing agent selected from at least one of an oxygen atom, a heterocycle, a C═N bond, and a C—O—C bond.
[0036] Item 10. The battery packaging material according to any one of Items 3 to 9, wherein the adhesive layer contains at least one selected from the group consisting of a polyurethane resin, an ester resin, and an epoxy resin.
[0037] Item 11. The battery packaging material according to any one of Items 1 to 10, wherein the barrier layer is composed of an aluminum foil.
[0038] Item 12. The battery packaging material according to any one of Items 1 to 11, wherein the resin constituting the thermally fusible resin layer contains a polyolefin skeleton.
[0039] Item 13. A method for producing a battery packaging material, comprising the step of laminating at least a base layer, a barrier layer, and a heat-fusible resin layer in this order to obtain a laminate,
[0040] When the barrier layer is laminated, an acid-resistant film is provided on at least one surface of the barrier layer. When the acid-resistant film is analyzed by time-of-flight secondary ion mass spectrometry, the acid-resistant film is derived from PO3 - The peak intensity P PO3 Relative to CrPO4 - The peak intensity P CrPO4 Ratio P PO3 / CrPO4 In the range of 6 to 120.
[0041] Item 14. A battery, wherein a battery element including at least a positive electrode, a negative electrode, and an electrolyte is housed in a packaging body formed of the battery packaging material according to any one of Items 1 to 12.
[0042] Item 15. Use of a laminate having at least a substrate layer, a barrier layer, and a heat-fusible resin layer in this order as a battery packaging material, wherein:
[0043] The barrier layer has an acid-resistant film on at least one surface thereof.
[0044] When the above acid-resistant film was analyzed by time-of-flight secondary ion mass spectrometry, the PO3 - The peak intensity P PO3 Relative to CrPO4 - The peak intensity P CrPO4 Ratio P PO3 / CrPO4 In the range of 6 to 120.
[0045] Effects of the Invention
[0046] According to the present invention, a battery packaging material having an acid-resistant film and a barrier layer having excellent long-term adhesion can be provided. In addition, according to the present invention, a method for producing the battery packaging material and a battery using the battery packaging material can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1 This is a schematic diagram showing an example of the cross-sectional structure of the battery packaging material of the present invention.
[0048] Figure 2 This is a schematic diagram showing an example of the cross-sectional structure of the battery packaging material of the present invention.
[0049] Figure 3 This is a schematic diagram showing an example of the cross-sectional structure of the battery packaging material of the present invention.
[0050] Figure 4 This is a schematic diagram showing an example of the cross-sectional structure of the battery packaging material of the present invention.
[0051] Figure 5 This is a schematic diagram showing an example of the cross-sectional structure of the battery packaging material of the present invention.
[0052] Explanation of symbols
[0053] 1 ... base material layer; 2 ... adhesive layer; 3 ... barrier layer; 3a, 3b ... acid-resistant film; 4 ... heat-fusible resin layer; 5 ... adhesive layer; 6 ... surface coating layer; 10 ... battery packaging material. DETAILED DESCRIPTION
[0054] The first aspect of the battery packaging material of the present invention is characterized in that it is composed of a laminate having at least a base layer, a barrier layer, and a heat-fusible resin layer in this order, and an acid-resistant film is provided on at least one surface of the barrier layer. When the acid-resistant film is analyzed by time-of-flight secondary ion mass spectrometry, the acid-resistant film is derived from PO3 - The peak intensity P PO3 Relative to CrPO4 - The peak intensity P CrPO4 Ratio P PO3 / CrPO4 In the range of 6 to 120.
[0055] In addition, the second aspect of the battery packaging material of the present invention is characterized in that it is composed of a laminate having at least a base layer, a barrier layer, and a heat-fusible resin layer in this order, and an acid-resistant film is provided on at least one surface of the barrier layer. When the acid-resistant film is analyzed by time-of-flight secondary ion mass spectrometry, the acid-resistant film is - The peak intensity P PO2 Relative to CrPO4 - The peak intensity P CrPO4 Ratio P PO2 / CrPO4 In the range of 7 to 70.
[0056] Below, refer to Figure 1 to Figure 5 , the battery packaging material, the method for producing the battery packaging material, and the battery using the battery packaging material of the present invention are described in detail.
[0057] In the present specification, a numerical range indicated by "to" means "above" or "below". For example, "2 to 15 mm" means 2 mm or more and 15 mm or less.
[0058] 1.Layered structure of battery packaging materials
[0059] The battery packaging material of the present invention is, for example, Figure 1 As shown in FIG. 1 , the battery packaging material is composed of a laminate having at least a base layer 1, a barrier layer 3, and a heat-fusible resin layer 4 in this order. In the battery packaging material of the present invention, the base layer 1 is the outermost layer, and the heat-fusible resin layer 4 is the innermost layer. That is, when assembling a battery, the heat-fusible resin layers 4 located at the periphery of the battery element are heat-fused to each other to seal the battery element, thereby encapsulating the battery element.
[0060] The barrier layer 3 has an acid-resistant film on at least one surface thereof. The acid-resistant film contains chromium. Figure 1 Schematic diagram showing a case where the surface of the barrier layer 3 on the side of the heat-fusible resin layer 4 in the battery packaging material of the present invention has an acid-resistant film 3a. Figure 2Schematic diagram showing a case where the barrier layer 3 has acid-resistant films 3a and 3b on both sides thereof in the battery packaging material of the present invention. In addition, as described later, in the battery packaging material of the present invention, the barrier layer 3 may have the acid-resistant film 3a only on the surface on the heat-fusible resin layer 4 side, the barrier layer 3 may have the acid-resistant film 3b only on the surface on the base material layer 1 side thereof, or the barrier layer 3 may have the acid-resistant films 3a and 3b on both sides thereof.
[0061] The battery packaging material of the present invention is Figure 3 As shown in FIG. 1 , an adhesive layer 2 may be provided between the substrate layer 1 and the barrier layer 3 for the purpose of improving the adhesion between them. Figure 4 As shown in FIG. 1 , an adhesive layer 5 may be provided between the barrier layer 3 and the heat-fusible resin layer 4, if necessary, for the purpose of improving the adhesiveness between them. Figure 5 As shown, for the purpose of improving design, electrolyte resistance, scratch resistance, moldability, etc., the substrate layer 1 may have a surface coating layer 6 on the side opposite to the barrier layer 3 as required.
[0062] The thickness of the laminate constituting the battery packaging material 10 of the present invention is not particularly limited. From the viewpoint of reducing the thickness of the battery packaging material to increase the energy density of the battery and to obtain a battery packaging material with excellent formability, for example, it can be about 180 μm or less, preferably about 150 μm or less, more preferably about 60 to 180 μm, and even more preferably about 60 to 150 μm.
[0063] It should be noted that, in the battery packaging material, regarding the barrier layer 3 described later, it is usually possible to determine the MD and TD during its manufacturing process. For example, when the barrier layer 3 is composed of aluminum foil, linear marks called rolling marks are generated on the surface of the aluminum foil in the rolling direction (RD: Rolling Direction) of the aluminum foil. Since the rolling marks extend along the rolling direction, the rolling direction of the aluminum foil can be grasped by observing the surface of the aluminum foil. In addition, in the manufacturing process of the laminate, usually, since the MD of the laminate is consistent with the RD of the aluminum foil, the rolling direction (RD) of the aluminum foil can be determined by observing the surface of the aluminum foil of the laminate, thereby determining the MD of the laminate. In addition, the TD of the laminate is a direction perpendicular to the MD of the laminate, thereby also determining the TD of the laminate.
[0064] 2. Forming the layers of battery packaging materials
[0065] [Base material layer 1]
[0066] In the battery packaging material of the present invention, the substrate layer 1 is a layer located on the outermost side. There is no particular restriction on the raw material forming the substrate layer 1 as long as it has insulating properties. As the raw material forming the substrate layer 1, for example, polyester resin, polyamide resin, epoxy resin, acrylic resin, fluororesin, polyurethane resin, silicone resin, phenolic resin, polycarbonate resin and resin films of mixtures and copolymers thereof can be cited. Among these, polyester resin and polyamide resin are preferably cited, and biaxially stretched polyester resin and biaxially stretched polyamide resin are more preferably cited. As polyester resin, polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polybutylene naphthalate, copolyester and the like can be specifically cited. In addition, as polyamide resin, nylon 6, nylon 66, copolymers of nylon 6 and nylon 66, nylon 6,10, polyamide MXD6 (poly(m-xylene adipamide)) and the like can be specifically cited.
[0067] The substrate layer 1 can be formed by one layer of resin film, but in order to improve the pinhole resistance and insulation, it can also be formed by more than two layers of resin film. Specifically, a multilayer structure of laminated polyester film and nylon film, a multilayer structure of multiple nylon films, a multilayer structure of multiple polyester films, etc. can be cited. When the substrate layer 1 is a multilayer structure, it is preferably a laminate of biaxially stretched nylon film and biaxially stretched polyester film, a laminate of multiple biaxially stretched nylon films, and a laminate of multiple biaxially stretched polyester films. For example, in the case of forming the substrate layer 1 by two layers of resin film, it is preferably a structure in which polyester resin is laminated with polyester resin, a structure in which polyamide resin is laminated with polyamide resin, or a structure in which polyester resin is laminated with polyamide resin, and more preferably a structure in which polyethylene terephthalate is laminated with polyethylene terephthalate, a structure in which nylon is laminated with nylon, or a structure in which polyethylene terephthalate is laminated with nylon. In addition, since polyester resin is not easily discolored when, for example, an electrolyte solution adheres to the surface, in this laminated structure, it is preferred to laminate the base layer 1 so that the polyester resin is located at the outermost layer. When the base layer 1 has a multilayer structure, the thickness of each layer is preferably about 2 to 25 μm.
[0068] When the substrate layer 1 is formed by a multilayer resin film, two or more layers of resin films can be laminated via adhesive components such as adhesives or adhesive resins. The type and amount of the adhesive components used are the same as those of the adhesive layer 2 described later. Among them, there is no particular restriction on the method of laminating two or more layers of resin films, and a known method can be used, for example, dry lamination method, sandwich lamination method, etc., preferably dry lamination method. In the case of lamination by dry lamination method, a polyurethane adhesive is preferably used as the adhesive layer. At this time, the thickness of the adhesive layer can be, for example, about 2 to 5 μm.
[0069] In the present invention, from the viewpoint of improving the moldability of the battery packaging material, a lubricant is preferably attached to the surface of the base layer 1. The lubricant is not particularly limited, but an amide lubricant is preferably used. Specific examples of the amide lubricant include the same substances as those exemplified in the heat-fusible resin layer 4 described later.
[0070] When a lubricant is present on the surface of the base layer 1, the amount of the lubricant is not particularly limited, but preferably about 3 mg / m 2 More preferably, 4 to 15 mg / m 2 About 5-14 mg / m 2 about.
[0071] The base layer 1 may contain a lubricant. The lubricant present on the surface of the base layer 1 may be a lubricant that oozes out of the lubricant contained in the resin constituting the base layer 1 or a lubricant that is applied on the surface of the base layer 1.
[0072] The thickness of the base material layer 1 is not particularly limited as long as it can function as a base material layer, and is, for example, about 3 to 50 μm, preferably about 10 to 35 μm.
[0073] [Adhesive layer 2]
[0074] In the battery packaging material 10 of the present invention, the adhesive layer 2 is a layer provided between the base layer 1 and the barrier layer 3 as necessary in order to firmly adhere them.
[0075] The adhesive layer 2 is formed of an adhesive capable of bonding the substrate layer 1 and the barrier layer 3. The adhesive used to form the adhesive layer 2 may be a two-component curing adhesive or a one-component curing adhesive. In addition, there is no particular limitation on the adhesive used to form the adhesive layer 2, and the adhesive may be a chemical reaction type, a solvent volatilization type, a hot melt type, a hot pressing type, or the like.
[0076] Specific examples of adhesive components that can be used to form the adhesive layer 2 include polyester resins such as polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polybutylene naphthalate, polyethylene isophthalate, and copolyesters; polyether resins; polyurethane resins; epoxy resins; phenolic resins; polycarbonate resins; polyamide resins such as nylon 6, nylon 66, nylon 12, and copolyamides; polyolefin resins such as polyolefins, carboxylic acid-modified polyolefins, and metal-modified polyolefins; polyvinyl acetate resins; cellulose adhesives; (meth) acrylic resins; polyimide resins; amino resins such as urea resins and melamine resins; rubbers such as chloroprene rubber, nitrile rubber, and styrene-butadiene rubber; silicone resins, etc. These adhesive components can be used alone or in combination of two or more. In addition, these resins that become bonding components can be used simultaneously with appropriate curing agents to improve bonding strength. The above-mentioned curing agent is appropriately selected from polyisocyanates, multifunctional epoxy resins, polymers containing oxazoline groups, polyamine resins, acid anhydrides, etc. according to the functional groups possessed by the bonding components. As these bonding components and curing agents, polyurethane-based adhesives containing various polyols and polyisocyanates are preferably cited. Further preferably, polyols such as polyester polyols, polyether polyols and acrylic polyols are used as main agents and aromatic or aliphatic polyisocyanates are used as curing agents of two-liquid curing polyurethane adhesives.
[0077] The thickness of the adhesive layer 2 is not particularly limited as long as it can function as an adhesive layer, and is, for example, about 1 to 10 μm, preferably about 2 to 5 μm.
[0078] [Barrier layer 3]
[0079] In the battery packaging material, the barrier layer 3 is a layer having the function of improving the strength of the battery packaging material and preventing water vapor, oxygen, light, etc. from invading the interior of the battery. The barrier layer 3 is preferably a metal layer, that is, a layer formed of metal. As the metal constituting the barrier layer 3, aluminum, stainless steel, titanium, etc. can be specifically mentioned, and aluminum is preferably mentioned. The barrier layer 3 can be formed, for example, of a metal foil, a metal vapor-deposited film, a film provided with these vapor-deposited films, etc., preferably formed of a metal foil, and more preferably formed of an aluminum alloy foil. When manufacturing the battery packaging material, from the viewpoint of preventing the barrier layer 3 from generating wrinkles and pinholes, the barrier layer is more preferably formed of a soft aluminum alloy foil such as annealed aluminum (JIS H4160: 1994A8021H-O, JIS H4160: 1994A8079H-O, JIS H4000: 2014A8021P-O, JIS H4000: 2014A8079P-O).
[0080] The thickness of the barrier layer 3 is not particularly limited as long as it can function as a barrier layer for water vapor or the like, but from the viewpoint of reducing the thickness of the battery packaging material, it is preferably about 100 μm or less, more preferably about 10 to 100 μm, and even more preferably about 10 to 80 μm.
[0081] [Acid-resistant films 3a, 3b]
[0082] In the battery packaging material of the present invention, an acid-resistant film is provided on at least one surface of the barrier layer 3. In the battery packaging material of the present invention, the acid-resistant film 3a may be provided only on the surface of the barrier layer 3 on the side of the heat-fusible resin layer 4, the acid-resistant film 3b may be provided only on the surface of the barrier layer 3 on the side of the base material layer 1, or the acid-resistant films 3a and 3b may be provided on both surfaces of the barrier layer 3.
[0083] The first aspect of the battery packaging material of the present invention is characterized in that, when the acid-resistant film is analyzed by time-of-flight secondary ion mass spectrometry, the PO3 - The peak intensity P PO3 Relative to CrPO4 - The peak intensity P CrPO4 Ratio P PO3 / CrPO4 In the range of 6 to 120. By making the peak intensity ratio in such a specific range, even when the electrolyte adheres to the battery packaging material, the long-term adhesion with the layer on the side where the acid-resistant film is provided adjacent to the barrier layer 3 is excellent. In addition, in the battery packaging material of the first embodiment of the present invention, the barrier layer having the acid-resistant film can maintain adhesion for a long time, and therefore, it is particularly useful as a packaging material for large batteries used in vehicles, etc.
[0084] In addition, the battery packaging material of the second embodiment of the present invention is characterized in that, when the acid-resistant film is analyzed by time-of-flight secondary ion mass spectrometry, the PO2 - The peak intensity P PO2 Relative to CrPO4 - The peak intensity P CrPO4 Ratio P PO2 / CrPO4 In the range of 7 to 70. PO2 / CrPO4 Within such a specific range, even when the electrolyte adheres to the battery packaging material, the long-term adhesion to the layer adjacent to the barrier layer 3 on the side provided with the acid-resistant film is excellent. In addition, in the battery packaging material of the second embodiment of the present invention, the barrier layer having the acid-resistant film can also maintain adhesion for a long time, and therefore, it is particularly useful as a packaging material for large batteries used in vehicles, etc.
[0085] In the first and second aspects of the present invention, when the barrier layer 3 has the acid-resistant films 3a and 3b on both sides, the peak intensity ratio P of the acid-resistant film on either side is PO3 / CrPO4 or P PO2 / CrPO4 Each of them may be within the above range (that is, in the case of the battery packaging material of the first embodiment, the peak intensity ratio P PO3 / CrPO4 In the case of the battery packaging material of the second embodiment, the peak intensity ratio P PO2 / CrPO4 It is preferred that both the acid-resistant films 3a and 3b satisfy the peak intensity ratio P PO3 / CrPO4 or P PO2 / CrPO4 In particular, the acid-resistant film on the heat-fusible resin layer side of the barrier layer and the adjacent layer (for example, the adhesive layer and the heat-fusible resin layer provided as required) are likely to have reduced adhesion due to the penetration of the electrolyte. In the battery packaging material of the present invention, it is preferred that the surface of at least the heat-fusible resin layer 4 side of the barrier layer 3 has an acid-resistant film 3a, and the acid-resistant film 3a preferably has a peak intensity ratio P PO2 / CrPO4 or P PO3 / CrPO4 These points also apply to the peak intensity ratios shown below.
[0086] In the first method, from PO3 - The peak intensity P PO3 Relative to CrPO4 - The peak intensity P CrPO4 Ratio P PO3 / CrPO4 The ratio P is preferably in the range of 6 to 120, and from the viewpoint of further improving the long-term adhesion of the barrier layer having an acid-resistant film. PO3 / CrPO4 The lower limit can be about 10 or more, and the upper limit can be preferably about 115 or less, more preferably about 110 or less, and further preferably about 50 or less. PO3 / CrPO4 Preferred ranges of include about 6 to 115, about 6 to 110, about 6 to 50, about 10 to 120, about 10 to 115, about 10 to 110, and about 10 to 50.
[0087] In addition, in the second method, from PO2 - The peak intensity P PO2 Relative to CrPO4 - The peak intensity P CrPO4 Ratio P PO2 / CrPO4 The ratio P is preferably in the range of 7 to 70, from the viewpoint of further improving the long-term adhesion of the barrier layer having an acid-resistant film. PO2 / CrPO4The lower limit is preferably about 10 or more, the upper limit is preferably about 65 or less, and more preferably about 25 or less. PO2 / CrPO4 Preferred ranges include about 7 to 65, about 7 to 25, about 10 to 70, about 10 to 65, and about 10 to 25.
[0088] Furthermore, in the first embodiment, when the acid-resistant film is analyzed by time-of-flight secondary ion mass spectrometry, the - The peak intensity P PO2 Relative to CrPO4 - The peak intensity P CrPO4 Ratio P PO2 / CrPO4 The lower limit is preferably about 7 or more, the upper limit is preferably about 70 or less, and more preferably about 65 or less. In the first embodiment, the ratio P PO2 / CrPO4 The range is preferably about 7 to 70, more preferably about 7 to 65.
[0089] The method of analyzing the acid-resistant films 3 a and 3 b by time-of-flight secondary ion mass spectrometry can be specifically performed using a time-of-flight secondary ion mass spectrometer under the following measurement conditions.
[0090] (Measurement conditions)
[0091] Primary ion: Doubly charged ion of bismuth cluster (Bi3 ++ )
[0092] 1st ion acceleration voltage: 30kV
[0093] Mass range (m / z): 0~1500
[0094] Measuring range: 100μm×100μm
[0095] Scan number: 16 times / cycle
[0096] Number of pixels (1 side): 256 pixels
[0097] Etching ions: Ar gas cluster ion beam (Ar-GCIB)
[0098] Etching ion acceleration voltage: 5.0kV
[0099] In addition, X-ray photoelectron spectroscopy can be used to confirm that the acid-resistant film contains chromium. Specifically, first, in the battery packaging material, the layers (adhesive layer, heat-melting resin layer, adhesive layer, etc.) laminated on the barrier layer are physically peeled off. Then, the barrier layer is placed in an electric furnace at about 300°C for about 30 minutes to remove the organic components present on the surface of the barrier layer. After that, the surface of the barrier layer is X-ray photoelectron spectroscopy to confirm that chromium is contained.
[0100] The acid-resistant films 3 a and 3 b can be formed by subjecting the surface of the barrier layer 3 to a chemical reaction treatment using a treatment solution containing a chromium compound such as chromium oxide.
[0101] As a chemical reaction surface treatment using a treatment solution containing a chromium compound, for example, there can be listed a method in which a treatment solution containing a chromium compound such as chromium oxide dispersed in phosphoric acid and / or its salt is applied to the surface of the barrier layer 3 and sintered to form an acid-resistant film on the surface of the barrier layer 3.
[0102] The peak intensity ratio P of the acid-resistant films 3a and 3b is PO3 / CrPO4 or P PO2 / CrPO4 , can be adjusted by, for example, the composition of the treatment solution for forming the acid-resistant films 3a and 3b, the temperature and time of the sintering treatment after the treatment, and other manufacturing conditions.
[0103] The ratio of the chromium compound to phosphoric acid and / or its salt in the treatment liquid containing the chromium compound is not particularly limited, but can be obtained by adjusting the peak intensity ratio P to the peak intensity ratio P. PO3 / CrPO4 or P PO2 / CrPO4 From the viewpoint of setting the above ranges, the ratio of phosphoric acid and / or its salt to 100 parts by mass of the chromium compound is preferably about 30 to 120 parts by mass, more preferably about 40 to 110 parts by mass. As phosphoric acid and its salt, for example, condensed phosphoric acid and its salt can be used.
[0104] In addition, the treatment solution containing the chromium compound may also contain an anionic polymer and a crosslinking agent for crosslinking the anionic polymer. As the anionic polymer, poly(meth)acrylic acid or its salt, a copolymer with (meth)acrylic acid or its salt as the main component, etc. may be cited. In addition, as the crosslinking agent, compounds with any functional group of isocyanate group, glycidyl group, carboxyl group, oxazoline group, silane coupling agent, etc. may be cited. The anionic polymer and the crosslinking agent may be one kind, or two or more kinds, respectively.
[0105] In addition, from the viewpoint of exerting excellent acid resistance and improving the long-term adhesion of the barrier layer having an acid-resistant film, the treatment liquid containing the chromium compound preferably contains an aminophenol polymer. In the treatment liquid containing the chromium compound, the content of the aminophenol polymer is preferably about 100 to 400 parts by mass, and more preferably about 200 to 300 parts by mass, relative to 100 parts by mass of the chromium compound. In addition, the weight average molecular weight of the aminophenol polymer is preferably about 5000 to 20000. It should be noted that the weight average molecular weight of the aminophenol polymer is a value obtained by gel permeation chromatography (GPC) under the condition of using polystyrene as a standard sample.
[0106] The solvent of the treatment liquid containing a chromium compound is not particularly limited as long as it is a solvent that can disperse the components contained in the treatment liquid and can be evaporated by subsequent heating, and water is preferably used. The solid content concentration of the treatment liquid containing a chromium compound can be, for example, about 1 to 15% by mass. In addition, the surface temperature of the barrier layer when the treatment liquid is applied to the surface of the barrier layer and then heated to form an acid-resistant film is preferably about 190 to 220°C, and the heating time is about 3 to 6 seconds. By adopting such a temperature and heating time, the solvent can be evaporated appropriately and the acid-resistant film layer can be well formed.
[0107] The solid content concentration of the chromium compound contained in the treatment solution for forming the acid-resistant film is not particularly limited, and can be selected from the range of the peak intensity ratio P to the peak intensity ratio P. PO3 / CrPO4 or P PO2 / CrPO4 From the viewpoint of achieving excellent acid resistance and improving the long-term adhesion of the barrier layer having an acid-resistant film by setting the above-specified ranges, preferably about 7.0 to 12.0 mass %, more preferably about 8.0 to 11.0 mass %, and even more preferably about 9.0 to 10.0 mass %.
[0108] The thickness of the acid-resistant film is not particularly limited, but from the viewpoint of being able to exert excellent acid resistance and improving the long-term adhesion of the barrier layer having the acid-resistant film, preferably about 1 nm to 10 μm, more preferably about 1 to 100 nm, and further preferably about 1 to 50 nm. The thickness of the acid-resistant film can be measured by observation using a transmission electron microscope, or by a combination of observation using a transmission electron microscope and energy dispersive X-ray spectroscopy or electron beam energy loss spectroscopy.
[0109] From the same point of view, the surface of the barrier layer 3 is 2 The amount of the acid-resistant film is preferably about 1 to 500 mg, more preferably about 1 to 100 mg, and even more preferably about 1 to 50 mg.
[0110] Examples of a method for applying the treatment liquid containing a chromium compound to the surface of the barrier layer include a bar coating method, a roll coating method, a gravure coating method, and a dipping method.
[0111] From the above peak intensity ratio P PO3 / CrPO4 or P PO2 / CrPO4From the viewpoint of achieving excellent acid resistance and improving the long-term adhesion of the barrier layer having the acid-resistant film by setting the temperature within the above-specified ranges, the heating temperature when the treatment liquid is sintered to form the acid-resistant film is preferably about 170 to 250° C., more preferably about 180 to 230° C. From the same viewpoint, the sintering time is preferably about 2 to 10 seconds, more preferably about 3 to 6 seconds.
[0112] From the viewpoint of more efficiently performing chemical surface treatment on the surface of the barrier layer, before providing an acid-resistant film on the surface of the barrier layer 3, it is preferred to perform a degreasing treatment by a known treatment method such as an alkali immersion method, an electrolytic washing method, an acid washing method, an electrolytic acid washing method, or an acid activation method.
[0113] [Thermal Fusible Resin Layer 4]
[0114] In the battery packaging material of the present invention, the heat-fusible resin layer 4 corresponds to the innermost layer and is a layer for sealing the battery element by heat-fusion bonding the heat-fusible resin layers to each other when assembling the battery.
[0115] There are no particular restrictions on the resin components used in the heat-fusible resin layer 4 as long as they can be heat-fused, and examples thereof include polyolefins, cyclic polyolefins, acid-modified polyolefins, and acid-modified cyclic polyolefins. That is, the resin constituting the heat-fusible resin layer 4 may contain a polyolefin skeleton, and preferably contains a polyolefin skeleton. Whether the resin constituting the heat-fusible resin layer 4 contains a polyolefin skeleton can be analyzed, for example, by infrared spectroscopy, gas chromatography-mass spectrometry, and the like, and there are no particular restrictions on the analysis method. For example, when measuring maleic anhydride-modified polyolefins by infrared spectroscopy, it is possible to obtain a polyolefin skeleton at a wave number of 1760 cm -1 Nearby and wave number 1780cm -1 A peak derived from maleic anhydride is detected near the 200 nm wavelength. However, when the degree of acid modification is low, the peak may become smaller and not be detected. In this case, analysis can be performed using nuclear magnetic resonance spectroscopy.
[0116] Specific examples of the polyolefin include polyethylene such as low-density polyethylene, medium-density polyethylene, high-density polyethylene, and linear low-density polyethylene; polypropylene such as homopolypropylene, block copolymers of polypropylene (e.g., block copolymers of propylene and ethylene), and random copolymers of polypropylene (e.g., random copolymers of propylene and ethylene); terpolymers of ethylene-butene-propylene, etc. Among these polyolefins, polyethylene and polypropylene are preferably used.
[0117] The cyclic polyolefin is a copolymer of an olefin and a cyclic monomer. Examples of the olefin as a constituent monomer of the cyclic polyolefin include ethylene, propylene, 4-methyl-1-pentene, butadiene, isoprene, and the like. In addition, examples of the cyclic monomer as a constituent monomer of the cyclic polyolefin include cyclic olefins such as norbornene, and specifically cyclic dienes such as cyclopentadiene, dicyclopentadiene, cyclohexadiene, and norbornene. Among these polyolefins, cyclic olefins are preferably used, and norbornene is more preferably used.
[0118] The acid-modified polyolefin is a polymer obtained by modifying the polyolefin by block copolymerization or graft copolymerization with an acid component such as carboxylic acid. Examples of the acid component used for modification include carboxylic acids or anhydrides thereof such as maleic acid, acrylic acid, itaconic acid, crotonic acid, maleic anhydride, and itaconic anhydride.
[0119] The acid-modified cyclic polyolefin is a polymer obtained by copolymerizing a part of the monomers constituting the cyclic polyolefin with an α,β-unsaturated carboxylic acid or its anhydride, or by block copolymerizing or graft copolymerizing the cyclic polyolefin with an α,β-unsaturated carboxylic acid or its anhydride. The cyclic polyolefin modified with carboxylic acid is the same as described above. In addition, the carboxylic acid used in the modification is the same as that used in the modification of the polyolefin.
[0120] Among these resin components, preferably, polyolefins such as polypropylene and carboxylic acid-modified polyolefins are used; more preferably, polypropylene and acid-modified polypropylene are used.
[0121] The heat-fusible resin layer 4 may be formed of a single resin component or a blended polymer of two or more resin components. In addition, the heat-fusible resin layer 4 may be formed of only one layer or two or more layers of the same or different resin components.
[0122] In the present invention, from the viewpoint of improving the moldability of the battery packaging material, a lubricant is preferably attached to the surface of the heat-fusible resin layer. There is no particular limitation on the lubricant, and an amide lubricant is preferably cited. Specific examples of amide lubricants include, for example, saturated fatty acid amides, unsaturated fatty acid amides, substituted amides, hydroxymethylamides, saturated fatty acid bisamides, unsaturated fatty acid bisamides, and the like. Specific examples of saturated fatty acid amides include lauramide, palmitamide, stearamide, behenamide, hydroxystearamide, and the like. Specific examples of unsaturated fatty acid amides include oleamide, erucamide, and the like. Specific examples of substituted amides include N-oleyl palmitamide, N-stearyl stearamide, N-stearyl oleamide, N-oleyl stearamide, N-stearyl erucamide, and the like. In addition, specific examples of hydroxymethylamides include hydroxymethyl stearamide, and the like. Specific examples of saturated fatty acid bisamides include methylene bisstearamide, ethylene biscaprylamide, ethylene bislaurylamide, ethylene bisstearamide, ethylene bishydroxystearamide, ethylene bisbehenamide, hexamethylene bisstearamide, hexamethylene bisbehenamide, hexamethylene hydroxystearamide, N,N'-distearyl adipamide, N,N'-distearyl sebacamide, etc. Specific examples of unsaturated fatty acid bisamides include ethylene bisoleamide, ethylene biserucamide, hexamethylene bisoleamide, N,N'-dioleyl adipamide, N,N'-dioleyl sebacamide, etc. Specific examples of fatty acid ester amides include stearamide stearic acid ethyl ester, etc. In addition, specific examples of aromatic bisamides include meta-xylene bisstearamide, meta-xylene bishydroxystearamide, N,N'-distearyl isophthalamide, etc. The lubricants may be used alone or in combination of two or more.
[0123] When a lubricant is present on the surface of the heat-fusible resin layer 4, the amount thereof is not particularly limited, but preferably about 3 mg / m 2 More preferably 4 to 15 mg / m 2 About 5 to 14 mg / m 2 about.
[0124] The heat-fusible resin layer 4 contains a lubricant. The lubricant on the surface of the heat-fusible resin layer 4 may be a lubricant that oozes out the lubricant contained in the resin constituting the heat-fusible resin layer 4 or a lubricant that is coated on the surface of the heat-fusible resin layer 4.
[0125] The thickness of the thermally fusible resin layer 4 is not particularly limited as long as it can function as a thermally fusible resin layer, but is preferably about 60 μm or less, more preferably about 15 to 60 μm, and even more preferably about 15 to 40 μm.
[0126] [Adhesive layer 5]
[0127] In the battery packaging material of the present invention, the adhesive layer 5 is provided between the barrier layer 3 and the heat-fusible resin layer 4 as necessary to improve the adhesion between them. The adhesive layer 5 may be composed of a single layer or a plurality of the same or different layers.
[0128] Generally speaking, from the viewpoint of improving the adhesion between the barrier layer and the heat-fusible resin layer, it is preferred to have an adhesive layer between them. However, when the surface of the heat-fusible resin layer side of the barrier layer has an acid-resistant film, there is a problem that the long-term adhesion between the acid-resistant film and the adhesive layer is easily reduced. In contrast, in the battery packaging material of the present invention, since the acid-resistant film has the above-mentioned specific peak intensity ratio P PO3 / CrPO4 or P PO2 / CrPO4 , thus the adhesion is excellent, and the long-term adhesion between the acid-resistant film 3a and the adhesive layer 5 is also effectively improved. That is, in the battery packaging material of the present invention, in the manner in which the acid-resistant film 3a on the surface of the barrier layer 3 and the heat-fusible resin layer 4 are laminated via the adhesive layer 5, the effect of the excellent long-term adhesion of the barrier layer having the acid-resistant film can be particularly effectively exerted.
[0129] The adhesive layer 5 is formed of a resin that can bond the barrier layer 3 (and the acid-resistant film 3a) and the heat-fusible resin layer 4. As the resin used to form the adhesive layer 5, regarding its bonding mechanism, the type of adhesive component, etc., the same mechanism and type as the adhesive exemplified in the adhesive layer 2 can be used. In addition, as the resin used to form the adhesive layer 5, polyolefin resins such as polyolefin, cyclic polyolefin, carboxylic acid-modified polyolefin, and carboxylic acid-modified cyclic polyolefin exemplified in the above-mentioned heat-fusible resin layer 4 can also be used. From the viewpoint of making the barrier layer 3 and the heat-fusible resin layer 4 have excellent adhesion, as the polyolefin, carboxylic acid-modified polyolefin is preferred, and carboxylic acid-modified polypropylene is particularly preferred. That is, the resin constituting the adhesive layer 5 may contain a polyolefin skeleton, and preferably contains a polyolefin skeleton. Whether the resin constituting the adhesive layer 5 contains a polyolefin skeleton can be analyzed, for example, by infrared spectroscopy, gas chromatography mass spectrometry, etc., and the analysis method is not particularly limited. For example, when measuring maleic anhydride-modified polyolefins by infrared spectroscopy, it is possible to obtain the -1 Nearby and wave number 1780cm -1A peak derived from maleic anhydride is detected near the surface of the precipitate. However, when the degree of acid modification is low, the peak may become smaller and not be detected. In this case, analysis can be performed using nuclear magnetic resonance spectroscopy.
[0130] Furthermore, from the viewpoint of reducing the thickness of the battery packaging material and making it a battery packaging material with excellent shape stability after molding, the adhesive layer 5 may be a cured product of a resin composition containing an acid-modified polyolefin and a curing agent. As the acid-modified polyolefin, the same carboxylic acid-modified polyolefin and carboxylic acid-modified cyclic polyolefin as exemplified in the thermally fusible resin layer 4 can be preferably exemplified.
[0131] The curing agent is not particularly limited as long as it is a substance that cures the acid-modified polyolefin, and examples of the curing agent include epoxy curing agents, polyfunctional isocyanate curing agents, carbodiimide curing agents, and oxazoline curing agents.
[0132] The epoxy curing agent is not particularly limited as long as it is a compound having at least one epoxy group. Examples of the epoxy curing agent include epoxy resins such as bisphenol A diglycidyl ether, modified bisphenol A diglycidyl ether, novolac glycidyl ether, glycerol polyglycidyl ether, and polyglycerol polyglycidyl ether.
[0133] The polyfunctional isocyanate curing agent is not particularly limited as long as it is a compound with more than 2 isocyanate groups. As a specific example of the polyfunctional isocyanate curing agent, isophorone diisocyanate (IPDI), hexamethylene diisocyanate (HDI), toluene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), the polymerized or ureate-esterified materials, their mixtures and copolymers with other polymers etc. can be listed.
[0134] The carbodiimide curing agent is not particularly limited as long as it is a compound having at least one carbodiimide group (-N=C=N-). As the carbodiimide curing agent, a polycarbodiimide compound having at least two or more carbodiimide groups is preferred.
[0135] Oxazoline curing agent is just not particularly limited as long as it is the compound with oxazoline skeleton (oxazoline group).As the specific example of the compound with oxazoline group, the material with polystyrene main chain, the material with acrylic acid main chain etc. can be enumerated.As oxazoline curing agent, specifically can enumerate the EPOCROS series etc. manufactured by Japan Catalyst Co., Ltd.
[0136] From the viewpoint of improving the adhesion between the barrier layer 3 and the heat-fusible resin layer 4 by the adhesive layer 5 , etc., the curing agent may be composed of two or more compounds.
[0137] The content of the curing agent in the resin composition forming the adhesive layer 5 is preferably in the range of about 0.1 to 50 mass %, more preferably in the range of about 0.1 to 30 mass %, and further preferably in the range of about 0.1 to 10 mass %.
[0138] In addition, the adhesive layer 5 is preferably a cured product of a resin composition containing an acid-modified polyolefin and at least one selected from a compound having an isocyanate group, a compound having an oxazoline group, and a compound having an epoxy group, and is particularly preferably a cured product of a resin composition containing an acid-modified polyolefin and at least one selected from a compound having an isocyanate group and a compound having an epoxy group. In addition, the adhesive layer 5 preferably contains at least one selected from a polyurethane resin, an ester resin, and an epoxy resin, and more preferably contains a polyurethane resin and an epoxy resin. As an ester resin, for example, an amide ester resin is preferred. Amide ester resins are generally generated by the reaction of a carboxyl group and an oxazoline group. The adhesive layer 5 is more preferably a cured product of a resin composition containing at least one of these resins and the above-mentioned acid-modified polyolefin. In addition, when there are unreacted products of curing agents such as compounds having an isocyanate group, compounds having an oxazoline group, and epoxy resins remaining in the adhesive layer 5, for example, the presence of unreacted products can be confirmed by a method selected from infrared spectroscopy, Raman spectroscopy, time-of-flight secondary ion mass spectrometry (TOF-SIMS), etc.
[0139] In addition, from the viewpoint of further improving the adhesion between the acid-resistant film 3a and the adhesive layer 5, the adhesive layer 5 is preferably a cured product of a resin composition containing a curing agent selected from at least one of an oxygen atom, a heterocycle, a C=N bond and a C-O-C bond. As a curing agent having a heterocycle, for example, a curing agent having an oxazoline group, a curing agent having an epoxy group, etc. can be cited. In addition, as a curing agent having a C=N bond, a curing agent having an oxazoline group, a curing agent having an isocyanate group, etc. can be cited. In addition, as a curing agent having a C-O-C bond, a curing agent having an oxazoline group, a curing agent having an epoxy group, a polyurethane resin, etc. can be cited. For example, it is possible to confirm that the adhesive layer 5 is a cured product of a resin composition containing these curing agents by methods such as gas chromatography-mass spectrometry (GCMS), infrared spectroscopy (IR), time-of-flight secondary ion mass spectrometry (TOF-SIMS), and X-ray photoelectron spectroscopy (XPS).
[0140] There is no particular restriction on the compound having an isocyanate group, and from the viewpoint of effectively improving the adhesion between the acid-resistant film 3a and the adhesive layer 5, a polyfunctional isocyanate compound can be preferably cited. The polyfunctional isocyanate compound is not particularly limited as long as it is a compound having two or more isocyanate groups. As a specific example of the polyfunctional isocyanate curing agent, the above-mentioned substances can be cited.
[0141] The content of the compound having an isocyanate group in the adhesive layer 5 is preferably in the range of 0.1 to 50 mass %, more preferably in the range of 0.5 to 40 mass % in the resin composition constituting the adhesive layer 5. This can effectively improve the adhesion between the acid-resistant film 3a and the adhesive layer 5.
[0142] The compound with oxazoline group is not particularly limited as long as it is a compound with oxazoline skeleton. As the specific example of the compound with oxazoline group, the material with polystyrene main chain, the material with acrylic acid main chain etc. can be enumerated. In addition, as commercially available product, the above-mentioned material etc. can be enumerated.
[0143] The proportion of the compound having an oxazoline group in the adhesive layer 5 is preferably in the range of 0.1 to 50 mass %, more preferably in the range of 0.5 to 40 mass % in the resin composition constituting the adhesive layer 5. This can effectively improve the adhesion between the acid-resistant film 3a and the adhesive layer 5.
[0144] As the epoxy resin, there is no particular limitation as long as it is a resin that can form a cross-linked structure through the epoxy groups present in the molecule, and a known epoxy resin can be used. As the weight average molecular weight of the epoxy resin, preferably about 50 to 2000, more preferably about 100 to 1000, and further preferably about 200 to 800. Among them, in the present invention, the weight average molecular weight of the epoxy resin is a value measured by gel permeation chromatography (GPC) using polystyrene as a standard sample.
[0145] Specific examples of epoxy resins include glycidyl ether derivatives of trimethylolpropane, bisphenol A diglycidyl ether, modified bisphenol A diglycidyl ether, novolac glycidyl ether, glycerol polyglycidyl ether, polyglycerol polyglycidyl ether, etc. The epoxy resins may be used alone or in combination of two or more.
[0146] The proportion of the epoxy resin in the adhesive layer 5 is preferably in the range of 0.1 to 50 mass %, more preferably in the range of 0.5 to 40 mass %, in the resin composition constituting the adhesive layer 5. This can effectively improve the adhesion between the acid-resistant film 3a and the adhesive layer 5.
[0147] In addition, in the present invention, when the adhesive layer 5 is a cured product of a resin composition containing at least one selected from a compound having an isocyanate group, a compound having an oxazoline group and an epoxy resin and the above-mentioned acid-modified polyolefin, the acid-modified polyolefin functions as a main agent, and the compound having an isocyanate group, the compound having an oxazoline group and the epoxy resin function as curing agents, respectively.
[0148] The thickness of the adhesive layer 5 is not particularly limited as long as it can function as an adhesive layer. When the adhesive exemplified in the adhesive layer 2 is used, it is preferably about 1 to 10 μm, and more preferably about 1 to 5 μm. In addition, when the resin exemplified in the heat-fusible resin layer 4 is used, it is preferably about 2 to 50 μm, and more preferably about 10 to 40 μm. In addition, in the case of a cured product of an acid-modified polyolefin and a curing agent, it is preferably about 30 μm or less, more preferably about 0.1 to 20 μm, and further preferably about 0.5 to 5 μm. Among them, when the adhesive layer 5 is a cured product of a resin composition containing an acid-modified polyolefin and a curing agent, the adhesive layer 5 can be formed by applying the resin composition and curing it by heating or the like.
[0149] [Surface coating layer 6]
[0150] In the battery packaging material of the present invention, a surface coating layer 6 may be provided as required on the outer side of the substrate layer 1 (the side of the substrate layer 1 opposite to the barrier layer 3) for the purpose of improving the appearance design, electrolyte resistance, scratch resistance, moldability, etc. When the surface coating layer 6 is provided, the surface coating layer 6 becomes the outermost layer of the battery packaging material.
[0151] The surface coating layer 6 can be formed by polyvinylidene chloride, polyester resin, polyurethane resin, acrylic resin, epoxy resin etc. for example. Among these, the surface coating layer 6 is preferably formed by 2 liquid curing resins. As the 2 liquid curing resins forming the surface coating layer 6, for example, 2 liquid curing polyurethane resins, 2 liquid curing polyester resins, 2 liquid curing epoxy resins etc. can be listed. In addition, additives can also be coordinated in the surface coating layer.
[0152] As additives, for example, microparticles with a particle size of about 0.5nm to 5μm can be listed. There is no particular restriction on the material of the additive, for example, metals, metal oxides, inorganic substances, organic substances, etc. can be listed. In addition, the shape of the additive is not particularly limited, for example, spherical, fibrous, plate-like, amorphous, hollow spherical, etc. can be listed. As additives, specifically, talc, silica, graphite, kaolin, montmorillonite, montmorillonite, synthetic mica, hydrotalcite, silica gel, zeolite, aluminum hydroxide, magnesium hydroxide, zinc oxide, magnesium oxide, aluminum oxide, neodymium oxide, antimony oxide, titanium oxide, cerium oxide, calcium sulfate, barium sulfate, calcium carbonate, calcium silicate, lithium carbonate, calcium benzoate, calcium oxalate, magnesium stearate, aluminum oxide, carbon black, carbon nanotubes, high melting point nylon, cross-linked acrylic acid, cross-linked styrene, cross-linked polyethylene, benzoguanamine, gold, aluminum, copper, nickel, etc. These additives can be used alone or in combination of two or more. Among these additives, silicon dioxide, barium sulfate, and titanium oxide are preferably used from the viewpoint of dispersion stability, cost, etc. In addition, the additives may be subjected to various surface treatments such as insulation treatment and high dispersibility treatment.
[0153] The content of the additive in the surface coating layer 6 is not particularly limited, but is preferably about 0.05 to 1.0 mass %, and more preferably about 0.1 to 0.5 mass %.
[0154] The method for forming the surface coating layer 6 is not particularly limited, and an example thereof is a method of applying a two-component curable resin forming the surface coating layer to the outer surface of the substrate layer 1. When an additive is added, the additive may be added to the two-component curable resin and mixed before application.
[0155] The thickness of the surface coating layer 6 is not particularly limited as long as the above-mentioned function as the surface coating layer 6 can be exhibited, and for example, it can be about 0.5 to 10 μm, and preferably about 1 to 5 μm.
[0156] 3. Method for manufacturing battery packaging material
[0157] The method for producing the battery packaging material of the present invention is not particularly limited as long as a laminated body formed by laminating layers of a predetermined composition can be obtained. For the first embodiment of the battery packaging material, the following method can be cited, namely, a process comprising laminating at least a base layer, a barrier layer, and a heat-fusible resin layer in this order to obtain a laminated body, wherein when the barrier layer is laminated, an acid-resistant film is provided on at least one surface of the barrier layer, and when the acid-resistant film is analyzed by time-of-flight secondary ion mass spectrometry, PO3 - The peak intensity P PO3 Relative to CrPO4 - The peak intensity P CrPO4Ratio P PO3 / CrPO4 In the range of 6 to 120.
[0158] In addition, the second embodiment of the battery packaging material includes a method comprising the steps of laminating at least a base material layer, a barrier layer, and a heat-fusible resin layer in this order to obtain a laminate, wherein when the barrier layer is laminated, an acid-resistant film is provided on at least one surface of the barrier layer, and when the acid-resistant film is analyzed by time-of-flight secondary ion mass spectrometry, the acid-resistant film is - The peak intensity P PO2 Relative to CrPO4 - The peak intensity P CrPO4 Ratio P PO2 / CrPO4 In the range of 7 to 70.
[0159] An example of a method for manufacturing a battery packaging material of the present invention is as follows. First, a laminate (hereinafter sometimes referred to as "laminate A") is formed by laminating a substrate layer 1, an adhesive layer 2 provided as required, and a barrier layer 3 in sequence. The formation of the laminate A can be specifically carried out by applying an adhesive for forming the adhesive layer 2 on the substrate layer 1 or the barrier layer 3 (the acid-resistant film 3a is used when the substrate layer 1 or the barrier layer 3 has an acid-resistant film 3a, and the explanation is omitted below) by a coating method such as a gravure coating method or a roller coating method. After drying, the adhesive layer 2 is cured after laminating the barrier layer 3 or the substrate layer 1. At this time, when laminating the barrier layer 3, a barrier layer having the above-mentioned acid-resistant film pre-formed on the surface of at least one side of the barrier layer 3 is used. In addition, the method for forming the acid-resistant films 3a and 3b is as described above.
[0160] Next, the heat-fusible resin layer 4 is laminated on the barrier layer 3 of the laminate A. When the heat-fusible resin layer 4 is laminated directly on the barrier layer 3, the resin component constituting the heat-fusible resin layer 4 can be coated on the barrier layer 3 of the laminate A by a gravure coating method, a roll coating method, or the like. In addition, when an adhesive layer 5 is provided between the barrier layer 3 and the heat-fusible resin layer 4, examples thereof include: (1) a method of laminating the adhesive layer 5 and the heat-fusible resin layer 4 on the barrier layer 3 of the laminate A by co-extrusion (co-extrusion lamination method); (2) a method of separately forming a laminate in which the adhesive layer 5 and the heat-fusible resin layer 4 are laminated, and laminating the laminate on the barrier layer 3 of the laminate A by a heat lamination method; (3) a method of laminating the adhesive layer 5 on the barrier layer 3 of the laminate A. (3) a method in which an adhesive for forming an adhesive layer 5 is laminated on the laminate A by an extrusion method or a solution coating method, and then dried at a high temperature and then sintered, and a heat-fusible resin layer 4 pre-filmed in a sheet form is laminated on the adhesive layer 5 by a heat lamination method; (4) a method in which the laminate A and the heat-fusible resin layer 4 pre-filmed in a sheet form are bonded together via the adhesive layer 5 while the molten adhesive layer 5 is flowed between the barrier layer 3 of the laminate A and the heat-fusible resin layer 4 pre-filmed in a sheet form (sandwich lamination method), etc.
[0161] When the surface coating layer 6 is provided, the surface coating layer is laminated on the surface of the substrate layer 1 on the opposite side to the barrier layer 3. The surface coating layer can be formed, for example, by applying the above-mentioned resin for forming the surface coating layer to the surface of the substrate layer 1. There is no particular restriction on the order of the process of laminating the barrier layer 3 on the surface of the substrate layer 1 and the process of laminating the surface coating layer on the surface of the substrate layer 1. For example, after the surface coating layer is formed on the surface of the substrate layer 1, the barrier layer 3 can be formed on the surface of the substrate layer 1 on the opposite side to the surface coating layer.
[0162] As described above, a laminated body is formed including a surface coating layer 6 arranged as required / a base material layer 1 / an adhesive layer 2 arranged as required / a barrier layer 3 having an acid-resistant coating on at least one surface / an adhesive layer 5 arranged as required / a heat-fusible resin layer 4. However, in order to strengthen the adhesion between the adhesive layer 2 and the adhesive layer 5 arranged as required, a heating treatment such as a hot roller contact type, a hot air type, a near infrared type or a far infrared type can also be performed.
[0163] In the battery packaging material of the present invention, each layer constituting the laminate may be subjected to a surface activation treatment such as corona discharge treatment, sandblasting treatment, oxidation treatment, ozone treatment, etc., as required, in order to improve or stabilize film forming properties, lamination processing, and adaptability to secondary processing (packaging, embossing molding) of the final product.
[0164] 4. Application of battery packaging materials
[0165] The battery packaging material of the present invention is used in a packaging body for sealing and storing battery elements such as a positive electrode, a negative electrode, and an electrolyte. That is, a battery can be made by storing battery elements including at least a positive electrode, a negative electrode, and an electrolyte in a packaging body formed using the battery packaging material of the present invention. In addition, in the battery packaging material of the present invention, the above-mentioned peak intensity and the like can be analyzed by cutting out the battery packaging material from the battery. When cutting out the battery packaging material from the battery, a sample is obtained from the top surface, bottom surface, and other parts of the battery where the heat-fusible resin layers are not heat-fused to each other for analysis.
[0166] Specifically, a battery element including at least a positive electrode, a negative electrode and an electrolyte is covered with the battery packaging material of the present invention in a state where metal terminals connected to the positive electrode and the negative electrode are protruding outward so as to form a flange portion (an area where the heat-fusible resin layers are in contact with each other) at the periphery of the battery element, and the heat-fusible resin layers of the flange portion are heat-sealed to each other to seal the battery element, thereby providing a battery using the battery packaging material. In the case where the battery element is housed in a packaging body formed by the battery packaging material of the present invention, the packaging body is formed in a manner such that the heat-fusible resin portion of the battery packaging material of the present invention is on the inside (the surface in contact with the battery element).
[0167] The battery packaging material of the present invention can be used in both primary and secondary batteries, and is preferably used in secondary batteries. The types of secondary batteries to which the battery packaging material of the present invention can be applied are not particularly limited, and examples thereof include lithium ion batteries, lithium ion polymer batteries, lead storage batteries, nickel-hydrogen storage batteries, nickel-cadmium storage batteries, nickel-iron storage batteries, nickel-zinc storage batteries, silver oxide-zinc storage batteries, metal-air batteries, multivalent cation batteries, capacitors, capacitors, etc. Among these secondary batteries, lithium ion batteries and lithium ion polymer batteries can be cited as preferred applicable objects of the battery packaging material of the present invention.
[0168] In the battery packaging material of the present invention, the barrier layer having the acid-resistant coating can maintain adhesion for a long period of time. Therefore, the battery packaging material of the present invention is particularly useful as a packaging material for large batteries used in vehicles such as hybrid cars and electric cars.
[0169] Example
[0170] The present invention will be described in detail below with reference to Examples and Comparative Examples, but the present invention is not limited to the Examples.
[0171] <Manufacturing of battery packaging materials>
[0172] Example 1
[0173] On the surface of a biaxially stretched nylon film (25 μm) as a substrate layer, a barrier layer composed of aluminum foil (JIS H4160: 1994A8021H-O, thickness 40 μm) having an acid-resistant coating (thickness 10 nm) chemically surface treated on both sides by the method described later is laminated by dry lamination. Specifically, a two-component polyurethane adhesive (polyol compound and aromatic isocyanate compound) is coated on one surface of the aluminum foil having an acid-resistant coating to form an adhesive layer (thickness 3 μm). Next, the adhesive layer on the barrier layer having an acid-resistant coating is laminated with the biaxially stretched nylon film side of the substrate layer, and then an aging treatment is performed to produce a laminate of biaxially stretched nylon film / adhesive layer / barrier layer having an acid-resistant coating on both sides.
[0174] Next, maleic anhydride-modified polypropylene and random polypropylene were coextruded to laminate maleic anhydride-modified polypropylene (23 μm) as an adhesive layer and random polypropylene (23 μm) as a heat-fusible resin layer on the barrier layer of the laminate. Next, the obtained laminate was aged to obtain a battery packaging material having a biaxially stretched nylon film (25 μm) / adhesive layer (3 μm) / barrier layer (40 μm) having an acid-resistant film (10 nm) on both sides / maleic anhydride-modified polypropylene (23 μm) / random polypropylene (23 μm) laminated in this order.
[0175] The formation of the acid-resistant film on the surface of the barrier layer is carried out as follows: a treatment liquid containing 43 parts by mass of an aminophenol polymer, 16 parts by mass of chromium fluoride, and 13 parts by mass of phosphoric acid relative to 100 parts by mass of water is prepared, and the treatment liquid is applied to both sides of the barrier layer (the film thickness after drying is 10 nm), and the surface temperature of the barrier layer reaches a temperature of about 190 to 230° C., and then heated and dried for about 3 to 6 seconds.
[0176] Example 2
[0177] As a substrate layer, a laminated film was prepared by laminating a biaxially stretched polyethylene terephthalate film (thickness 12 μm) and a biaxially stretched nylon film (thickness 15 μm) by dry lamination. In the laminated film, the biaxially stretched polyethylene terephthalate film and the biaxially stretched nylon film were bonded by a polyurethane adhesive (thickness after curing was 3 μm) using a polyol and an isocyanate curing agent. Next, a metal foil composed of aluminum foil (JIS H4160: 1994A8021H-O, thickness 40 μm) having an acid-resistant film (thickness 10 nm) by chemical surface treatment in the same manner as in Example 1 was laminated on both sides of the biaxially stretched nylon film by dry lamination. Specifically, a two-component polyurethane adhesive (polyol compound and aromatic isocyanate compound) was applied to one surface of an aluminum foil having an acid-resistant film, and an adhesive layer (3 μm thick) was formed on a barrier layer having an acid-resistant film (10 nm thick). Next, the adhesive layer on the barrier layer was laminated to the biaxially stretched nylon film side of the substrate layer, and then an aging treatment was performed to produce a laminate of biaxially stretched polyethylene terephthalate film / adhesive / biaxially stretched nylon film / adhesive layer / barrier layer.
[0178] Next, on the barrier layer of the obtained laminate, maleic anhydride-modified polypropylene (thickness 40 μm) as an adhesive layer and random polypropylene (thickness 40 μm) as a heat-fusible resin layer were coextruded to laminate the adhesive layer / heat-fusible resin layer on the barrier layer. Next, by aging the obtained laminate, a battery packaging material having biaxially stretched polyethylene terephthalate film (12 μm) / adhesive (3 μm) / biaxially stretched nylon film (15 μm) / adhesive layer (3 μm) / barrier layer (40 μm) having an acid-resistant film (thickness 10 nm) on both sides / maleic anhydride-modified polypropylene (40 μm) / random polypropylene (40 μm) laminated in this order was obtained.
[0179] Example 3
[0180] As in Example 1, first, a laminate of biaxially stretched nylon film / adhesive layer / barrier layer having acid-resistant coating on both sides was prepared. Next, an adhesive (thickness after curing is 3 μm) containing a non-crystalline polyolefin resin having a carboxyl group and a multifunctional isocyanate compound was applied as an adhesive layer on the surface of the acid-resistant coating of the obtained laminate, and the adhesive was dried. On the adhesive side of the laminate, an unstretched laminated polypropylene film (random polypropylene (thickness 5 μm) / block polypropylene (thickness 30 μm) / random polypropylene (thickness 5 μm), total thickness 40 μm) was laminated as a thermally fusible resin layer, and the film was passed between two heated rollers for bonding, thereby laminating an adhesive layer / thermo-fusible resin layer on the barrier layer. Next, by aging the obtained laminate, a battery packaging material is obtained which is laminated in this order: biaxially stretched polyethylene terephthalate film (12 μm) / adhesive (3 μm) / biaxially stretched nylon film (15 μm) / adhesive layer (3 μm) / barrier layer (40 μm) having an acid-resistant coating (thickness 10 nm) on both sides / adhesive layer (3 μm) / unstretched random polypropylene film (40 μm).
[0181] In Example 3, the acid-resistant film was formed on the surface of the barrier layer in the same manner as in Example 1 except that the phosphoric acid was approximately 0.9 times that in Example 1 (mass ratio).
[0182] Embodiment 4, 5
[0183] Regarding the formation of the acid-resistant film on the surface of the barrier layer in Example 1, in Example 4, the phosphoric acid was changed to about 1 / 2 times (mass ratio) of that in Example 1, and in Example 5, the phosphoric acid was changed to about 1.3 times (mass ratio) of that in the example. The same operations were carried out as in Example 1 to obtain battery packaging materials.
[0184] Comparative Example 1
[0185] As a substrate layer, a laminated film prepared by coextrusion lamination of polyethylene terephthalate and nylon and then biaxial stretching is prepared. In the laminated film, the biaxially stretched polyethylene terephthalate film (thickness 5 μm) and the biaxially stretched nylon film (thickness 20 μm) are bonded by using an adhesive layer (adhesive, thickness 1 μm) of a resin composition containing a modified thermoplastic resin graft-modified with an unsaturated carboxylic acid derivative component. Next, a barrier layer composed of aluminum foil (JIS H4160: 1994A8021H-O, thickness 40 μm) having an acid-resistant film (thickness 10 nm) containing cerium by chemical surface treatment on both sides by the method described later is laminated on the surface of the biaxially stretched nylon film side by a dry lamination method. Specifically, a two-component polyurethane adhesive (polyol compound and aromatic isocyanate compound) was applied on one surface of an aluminum foil having an acid-resistant coating to form an adhesive layer (3 μm thick). Next, the adhesive layer on the barrier layer having an acid-resistant coating was laminated with the biaxially stretched nylon film side of the substrate layer and then subjected to an aging treatment to prepare a laminate of biaxially stretched polyethylene terephthalate film / adhesive / biaxially stretched nylon film / adhesive layer / barrier layer having an acid-resistant coating on both sides.
[0186] Next, an adhesive (thickness after curing: 3 μm) containing a non-crystalline polyolefin resin having a carboxyl group and a multifunctional isocyanate compound was applied as an adhesive layer on the surface of the acid-resistant film of the obtained laminate, and then dried. On the adhesive side of the laminate, an unstretched laminated polypropylene film (random polypropylene (thickness 5 μm) / block polypropylene (thickness 30 μm) / random polypropylene (thickness 5 μm), total thickness 40 μm) was laminated as a thermally fusible resin layer, and the films were passed between two heated rollers for bonding, thereby laminating an adhesive layer / thermal fusible resin layer on the barrier layer. Next, by curing (aging) the obtained laminate, a battery packaging material is obtained which is laminated in this order: biaxially stretched polyethylene terephthalate film (5 μm) / adhesive (1 μm) / biaxially stretched nylon film (20 μm) / adhesive layer (3 μm) / barrier layer having an acid-resistant coating (thickness 10 nm) on both sides (40 μm) / adhesive layer (3 μm) / unstretched laminated polypropylene film (40 μm).
[0187] In Comparative Example 1, the formation of the acid-resistant film on the surface of the barrier layer was performed as follows: a treatment liquid (containing water as a solvent and having a solid content concentration of about 10% by mass) containing 20 parts by mass of an inorganic phosphorus compound (sodium phosphate) relative to 100 parts by mass of cerium oxide was prepared, and the treatment liquid was applied to both sides of the barrier layer (film thickness after drying was 20 nm) so that the surface temperature of the barrier layer reached a temperature of about 190 to 230° C., and heat drying was performed for about 3 to 6 seconds.
[0188] Comparative Example 2
[0189] A battery packaging material was obtained by laminating biaxially stretched polyethylene terephthalate film (5 μm) / adhesive (1 μm) / biaxially stretched nylon film (20 μm) / adhesive layer (3 μm) / barrier layer (40 μm) having an acid-resistant film (10 nm thick) on both sides / adhesive layer (3 μm) / unstretched laminated polypropylene film (80 μm) in this order except that an unstretched laminated polypropylene film (random polypropylene (10 μm thick) / block polypropylene (60 μm thick) / random polypropylene (10 μm thick), with a total thickness of 80 μm) was used instead of the unstretched laminated polypropylene film (40 μm thick) as the heat-fusible resin layer. As the aluminum foil of the barrier layer, an aluminum foil having the same acid-resistant film as that of Comparative Example 1 was used.
[0190] Comparative Examples 3 and 4
[0191] Regarding the formation of the acid-resistant film on the surface of the barrier layer in Example 1, in Comparative Example 3, the phosphoric acid was changed to about 1 / 3 times (mass ratio) that of Example 1, and in Comparative Example 4, the phosphoric acid was changed to about 1.5 times (mass ratio) that of the example. The same operations were carried out as in Example 1 to obtain battery packaging materials.
[0192] <Time-of-flight secondary ion mass spectrometry>
[0193] The acid-resistant film was analyzed as follows. First, the barrier layer and the adhesive layer were peeled off. At this time, water, organic solvents, acid or alkali aqueous solutions, etc. were not used, but the peeling was performed by physical means. After the barrier layer and the adhesive layer were peeled off, since the adhesive layer remained on the surface of the barrier layer, the remaining adhesive layer was removed by etching using Ar-GCIB. The surface of the barrier layer obtained in this way was analyzed by time-of-flight secondary ion mass spectrometry. - PO2 - and PO3 - The peak intensity P CrPO4 , P PO2 , P PO3 , and peak intensity P PO2 Relative to the peak intensity P CrPO4 The ratio of P PO2 / CrPO4 , and peak intensity P PO3 Relative to the peak intensity P CrPO4 The ratio of P PO3 / CrPO4 They are shown in Table 1. In Comparative Examples 1 and 2, cerium was used in the treatment solution for the chemical reaction treatment instead of chromium. Therefore, in Table 1, CrPO4- The peak intensity P CrPO4 Items with a “-” are shown.
[0194] The details of the measuring apparatus and measuring conditions of the time-of-flight secondary ion mass spectrometry are as follows.
[0195] Measuring device: TOF.SIMS5, a time-of-flight secondary ion mass spectrometer manufactured by ION-TOF
[0196] (Measurement conditions)
[0197] Primary ion: Doubly charged ion of bismuth cluster (Bi3 ++ )
[0198] 1st ion acceleration voltage: 30kV
[0199] Mass range (m / z): 0~1500
[0200] Measuring range: 100μm×100μm
[0201] Scan number: 16 times / cycle
[0202] Number of pixels (1 side): 256 pixels
[0203] Etching ions: Ar gas cluster ion beam (Ar-GCIB)
[0204] Etching ion acceleration voltage: 5.0kV
[0205] <Evaluation of Adhesion>
[0206] Evaluation of the adhesion between the barrier layer and the heat-fusible resin layer when the electrolyte solution adhered to the battery packaging material was performed by measuring the peel strength (N / 15 mm) in the following method.
[0207] First, each battery packaging material obtained above was cut into 15 mm (TD: Transverse Direction, horizontal direction) and 100 mm (MD: Machine Direction, vertical direction) sizes to prepare test pieces. The test pieces were placed in a glass bottle, and then an electrolyte solution was added (lithium 6-fluorophosphate (concentration of 1×10 3 mol / m 3 )) to immerse the entire test piece in the electrolyte. Seal the glass bottle in this state with a cap. Place the sealed glass bottle in an oven set at 85°C and leave it for 24 hours. Next, take the glass bottle out of the oven, take the test piece out of the glass bottle and wash it with water, and wipe the moisture on the surface of the test piece with a towel.
[0208] Next, the heat-fusible resin layer and the barrier layer of the test piece were peeled off, and the heat-fusible resin layer side and the barrier layer side of the test piece were stretched in a 180° direction at a speed of 50 mm / min with a distance between the markings of 50 mm using a tensile tester (manufactured by Shimadzu Corporation), and the peel strength of the test piece (N / 15mm) was measured. The peel strength of the test piece was measured within 10 minutes after the moisture on the surface of the test piece was wiped off with a towel. The strength when the distance between the markings reached 57 mm was taken as the peel strength of the test piece.
[0209] On the other hand, the initial adhesion is evaluated as described below. First, each battery packaging material obtained in Examples 1 to 5 and Comparative Examples 1 and 2 is cut into sizes of 15 mm (TD) and 100 mm (MD) to prepare test pieces. Next, the heat-fusible resin layer and the barrier layer of the test piece are peeled off, and the heat-fusible resin layer and the barrier layer are stretched in a direction of 180° at a speed of 50 mm / min with a distance between markings of 50 mm using a tensile testing machine (trade name AGS-XPlus manufactured by Shimadzu Corporation), and the peel strength (N / 15 mm) of the test piece is measured as the initial adhesion. The results are shown in Table 1. Taking the peel strength of the initial adhesion as 100%, the maintenance rate of the peel strength of the adhesion after immersion in the electrolyte and the peel strength (after 24 hours, 72 hours or 168 hours) are also shown in Table 1. When the thermally fusible resin layer and the barrier layer are peeled off, the adhesive layer between these layers is laminated with either or both of the thermally fusible resin layer and the barrier layer.
[0210] [Table 1]
[0211]
[0212] From the results shown in Table 1, it can be seen that the surface of the barrier layer has an acid-resistant film. When the acid-resistant film is analyzed by time-of-flight secondary ion mass spectrometry, the PO3 - The peak intensity P PO3 Relative to CrPO4 - The peak intensity P CrPO4 Ratio P PO3 / CrPO4 Although the surface of the barrier layer of the battery packaging materials of Examples 1 to 5 in the range of 6 to 120 has an acid-resistant film, the long-term adhesion between the barrier layer and the heat-fusible resin layer after immersion in the electrolyte is excellent. - The peak intensity P PO2 Relative to CrPO4 - The peak intensity PCrPO4 Ratio P PO2 / CrPO4 When the molecular weight is within the range of 7 to 70, the long-term adhesion between the barrier layer and the thermally fusible resin layer is excellent.
Claims
1. A battery packaging material, characterized in that: The invention is composed of a laminated body having at least a base material layer, a barrier layer, and a heat-fusible resin layer in this order. The barrier layer has an acid-resistant film on at least one surface thereof. When the acid-resistant film was analyzed by time-of-flight secondary ion mass spectrometry, the PO3 - The peak intensity P PO3 Relative to CrPO4 - The peak intensity P CrPO4 Ratio P PO3 / CrPO4 In the range of 6 to 120, When the acid-resistant film was analyzed by time-of-flight secondary ion mass spectrometry, the PO2 - The peak intensity P PO2 Relative to CrPO4 - The peak intensity P CrPO4 Ratio P PO2 / CrPO4 In the range of 7 to 70, The acid-resistant film contains a chromium compound, phosphoric acid and / or its salt, and an aminophenol polymer.
2. The battery packaging material according to claim 1, wherein: The substrate layer contains at least one of polyester and polyamide.
3. A battery packaging material, characterized in that: The invention is composed of a laminated body having at least a base material layer, a barrier layer, and a heat-fusible resin layer in this order. The substrate layer is formed of a single layer of polyester film, or a two-layer structure of a polyester film and a nylon film, or a two-layer structure of a nylon film. The barrier layer has an acid-resistant film on at least one surface thereof. When the acid-resistant film was analyzed by time-of-flight secondary ion mass spectrometry, the PO3 - The peak intensity P PO3 Relative to CrPO4 - The peak intensity P CrPO4 Ratio P PO3 / CrPO4 In the range of 6 to 120, When the acid-resistant film was analyzed by time-of-flight secondary ion mass spectrometry, the PO2 - The peak intensity P PO2 Relative to CrPO4 - The peak intensity P CrPO4 Ratio P PO2 / CrPO4 In the range of 7 to 70, The acid-resistant film contains a chromium compound, phosphoric acid and / or its salt, and an aminophenol polymer.
4. A battery packaging material, characterized in that: The invention is composed of a laminated body having at least a surface coating layer, a base material layer, a barrier layer, and a heat-fusible resin layer in this order. The substrate layer comprises polyamide, The barrier layer has an acid-resistant film on at least one surface thereof. When the acid-resistant film was analyzed by time-of-flight secondary ion mass spectrometry, the PO3 - The peak intensity P PO3 Relative to CrPO4 - The peak intensity P CrPO4 Ratio P PO3 / CrPO4 In the range of 6 to 120, When the acid-resistant film was analyzed by time-of-flight secondary ion mass spectrometry, the PO2 - The peak intensity P PO2 Relative to CrPO4 - The peak intensity P CrPO4 Ratio P PO2 / CrPO4 In the range of 7 to 70, The acid-resistant film contains a chromium compound, phosphoric acid and / or its salt, and an aminophenol polymer.
5. The battery packaging material according to any one of claims 1 to 4, characterized in that: The thickness of the substrate layer is 3 μm or more and 50 μm or less.
6. The battery packaging material according to any one of claims 1 to 4, wherein: The thickness of the substrate layer is not less than 10 μm and not more than 35 μm.
7. The battery packaging material according to any one of claims 1 to 4, wherein: The thickness of the substrate layer is greater than 35 μm and less than or equal to 50 μm.
8. The battery packaging material according to any one of claims 1 to 4, wherein: There is a lubricant on the surface of the substrate layer, and the amount of the lubricant is 3 mg / m 2 above.
9. The battery packaging material according to any one of claims 1 to 4, characterized in that: The thermally fusible resin layer includes at least one selected from the group consisting of polyolefin, cyclic polyolefin, acid-modified polyolefin, and acid-modified cyclic polyolefin.
10. The battery packaging material according to any one of claims 1 to 4, characterized in that: The thermally fusible resin layer is formed of two or more layers of the same or different resins.
11. The battery packaging material according to any one of claims 1 to 4, characterized in that: There is a lubricant on the surface of the thermally fusible resin layer, and the amount of the lubricant is 3 mg / m 2 More than 15 mg / m 2 the following.
12. The battery packaging material according to any one of claims 1 to 4, characterized in that: Two or more lubricants are present on the surface of the thermally fusible resin layer.
13. The battery packaging material according to any one of claims 1 to 4, characterized in that: An adhesive layer is provided between the barrier layer and the heat-fusible resin layer, The adhesive layer is composed of a resin containing a polyolefin skeleton.
14. The battery packaging material according to any one of claims 1 to 4, wherein: An adhesive layer is provided between the barrier layer and the heat-fusible resin layer, The adhesive layer includes at least one selected from the group consisting of polyolefin, cyclic polyolefin, acid-modified polyolefin and acid-modified cyclic polyolefin.
15. The battery packaging material according to any one of claims 1 to 4, characterized in that: An adhesive layer is provided between the barrier layer and the heat-fusible resin layer, The heat-fusible resin layer is formed of two or more layers of the same or different resins. The adhesive layer and the heat-fusible resin layer are a co-extruded laminate.
16. The battery packaging material according to any one of claims 1 to 4, wherein: An adhesive layer is provided between the barrier layer and the heat-fusible resin layer, The adhesive layer and the heat-fusible resin layer are formed by any one of (1) coextrusion, (2) heat lamination, and (3) sandwich lamination.
17. The battery packaging material according to any one of claims 1 to 4, wherein: At least the surface of the barrier layer on the thermally fusible resin layer side has the acid-resistant coating.
18. The battery packaging material according to claim 17, wherein: The acid-resistant film and the heat-fusible resin layer are laminated with an adhesive layer interposed therebetween.
19. The battery packaging material according to claim 18, wherein: The resin constituting the adhesive layer has a polyolefin skeleton.
20. The battery packaging material according to claim 18, wherein: The adhesive layer contains acid-modified polyolefin.
21. The battery packaging material according to claim 18, wherein: When the adhesive layer was analyzed by infrared spectroscopy, a peak derived from maleic anhydride was detected.
22. The battery packaging material according to claim 20, wherein: The acid-modified polyolefin of the adhesive layer is maleic anhydride-modified polypropylene. The thermally fusible resin layer contains polypropylene.
23. The battery packaging material according to claim 18, wherein: The adhesive layer is a cured product of a resin composition containing at least one selected from a compound having an isocyanate group, a compound having an oxazoline group, and a compound having an epoxy group.
24. The battery packaging material according to claim 18, wherein: The adhesive layer is a cured product of a resin composition containing a curing agent having at least one selected from an oxygen atom, a heterocyclic ring, and a C═N bond.
25. The battery packaging material according to claim 24, wherein: The adhesive layer is a cured product of a resin composition containing a curing agent having at least one selected from a heterocyclic ring, a C═N bond, and a C—O—C bond.
26. The battery packaging material according to claim 18, wherein: The adhesive layer contains at least one selected from the group consisting of polyurethane resin, ester resin and epoxy resin.
27. The battery packaging material according to any one of claims 1 to 4, wherein: The barrier layer is composed of at least one of an aluminum alloy foil and a stainless steel foil.
28. The battery packaging material according to any one of claims 1 to 4, wherein: The resin constituting the thermally fusible resin layer contains a polyolefin skeleton.
29. The battery packaging material according to any one of claims 1 to 4, wherein: When the acid-resistant film was analyzed by time-of-flight secondary ion mass spectrometry, the PO3 - The peak intensity P PO3 Relative to CrPO4 - The peak intensity P CrPO4 Ratio P PO3 / CrPO4 In the range of 10 to 115.
30. The battery packaging material according to any one of claims 1 to 4, wherein: A lubricant is present on at least one of a surface of the base material layer and a surface of the thermally fusible resin layer.
31. The battery packaging material according to claim 30, wherein: The lubricant includes at least one selected from the group consisting of saturated fatty acid amide, unsaturated fatty acid amide, substituted amide, hydroxymethyl amide, saturated fatty acid bisamide, unsaturated fatty acid bisamide, fatty acid ester amide and aromatic bisamide.
32. The battery packaging material according to any one of claims 1 to 4, wherein: The thickness of the barrier layer is less than 100 μm.
33. The battery packaging material according to any one of claims 1 to 4, characterized in that: The thickness of the barrier layer is greater than or equal to 10 μm and less than or equal to 100 μm. The thickness of the barrier layer is 10 μm or more and 40 μm or less, or more than 40 μm and 100 μm or less.
34. The battery packaging material according to any one of claims 1 to 4, wherein: Two or more lubricants are present on the surface of the base material layer.
35. A method for manufacturing a battery packaging material, characterized in that: The method comprises the steps of laminating at least a base material layer, a barrier layer, and a heat-fusible resin layer in this order to obtain a laminate. When the barrier layer is laminated, the surface of at least one side of the barrier layer has an acid-resistant film. When the acid-resistant film is analyzed by time-of-flight secondary ion mass spectrometry, the acid-resistant film is derived from PO3 - The peak intensity P PO3 Relative to CrPO4 - The peak intensity P CrPO4 Ratio P PO3 / CrPO4 In the range of 6 to 120, from PO2 - The peak intensity P PO2 Relative to CrPO4 - The peak intensity P CrPO4 Ratio P PO2 / CrPO4 In the range of 7 to 70, the acid-resistant film contains a chromium compound, phosphoric acid and / or its salt, and an aminophenol polymer.
36. A battery, characterized in that: A battery element including at least a positive electrode, a negative electrode, and an electrolyte is housed in a packaging body formed of the battery packaging material according to any one of claims 1 to 34.
Citation Information
Patent Citations
Layered package material, outer package material for battery, and the battery
JP2008287971A
Battery packaging material
CN105144422A
Battery packaging materials, manufacturing methods of battery packaging materials, and batteries
CN110945678B